2014
DOI: 10.1371/journal.pone.0100386
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Pharmacological Evaluation of Novel Vanadium-Containing Complexes as Antidiabetic Agents

Abstract: Based on the data about structure and antidiabetic activity of twenty seven vanadium and zinc coordination complexes collected from literature we developed QSAR models using the GUSAR program. These QSAR models were applied to 10 novel vanadium coordination complexes designed in silico in order to predict their hypoglycemic action. The five most promising substances with predicted potent hypoglycemic action were selected for chemical synthesis and pharmacological evaluation. The selected coordination vanadium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…V cytotoxicity is well known and it depends on its degree of oxidation and chemical form (organic or inorganic) (Goc, 2006). Recently, two V (IV and V) compounds were synthesized that showed potent hypoglycemic activities and moderate toxic effects in a rat model (Fedorova et al, 2014). On the other hand, Voroshilin et al (1978) reported a genotoxic dose of 10 μg ml -1 tungstate on human lymphocytes.…”
Section: Testing Polyoxometalates Cytotoxicity By Mtt Assaymentioning
confidence: 99%
“…V cytotoxicity is well known and it depends on its degree of oxidation and chemical form (organic or inorganic) (Goc, 2006). Recently, two V (IV and V) compounds were synthesized that showed potent hypoglycemic activities and moderate toxic effects in a rat model (Fedorova et al, 2014). On the other hand, Voroshilin et al (1978) reported a genotoxic dose of 10 μg ml -1 tungstate on human lymphocytes.…”
Section: Testing Polyoxometalates Cytotoxicity By Mtt Assaymentioning
confidence: 99%
“…Vanadium is an essential trace element that is involved in numerous biological processes in plants, mammals and microorganisms [9]. Vanadium-based compounds exhibit a broad range of pharmacological activities, namely, antioxidant property, anticarcinogenic effect, lowering of cholesterol, triglycerides and glucose levels, diuretic effect, contraction of blood vessels, enhancement of oxygen-affinity of hemoglobin and myoglobin, etc [9,10]. Vanadium also functions as an oxidation-reduction catalyst [11].…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium, a transition metal, is a biologically important element incorporated in a number of physiological processes. Vanadium compounds, in particular organic derivatives, are effective in various diseases like diabetes, cancer, hypertension, Ischemia and Myocardial Stroke (45). The formation of a complex between metals and flavonoids plays an important role to forage free radicals as compared to the parent molecule resulting in reduced toxicity of the metals (46).…”
Section: Discussionmentioning
confidence: 99%